The role of information networks along the poultry value chain - Birol, Ekin; Tiongco, Marites (International Food Policy Research Institute, 2008)
Mapping the flow of information along the poultry value chain is crucial for the identification of the actors to whom highly pathogenic avian influenza (HPAI) risks should be communicated. Each actor in the poultry sector, whether private and public, or formal or informal, has particular roles in the risk-communication process. Network mapping exercises help to identify the different actors involved in the poultry value chain, and to understand their roles, linkages, and influence in communicating disease risk information. Consequently, IFPRI and ILRI conducted network mapping exercises with participants of multistakeholder workshops held in Ghana, Ethiopia, Kenya, and Nigeria.; The following questions were discussed:; What formal, informal, private, and public actors are involved in the live poultry value chain?; What are the flows of goods between various actors?; How does communication on disease information flow in the value chain?; Who in the value chain is influential in the communication of information about HPAI?; What should be improved to make the value chain more resilient against the effects of HPAI and HPAI scare?; Where and how can project findings help inform decisionmaking in the value chain?; This brief highlights and summarizes the main findings of these network maps (Net-Maps). The Net-Maps were drawn based on the participants’ expert opinions as well as their experience with past interventions.